Prevalence and Correlation of Knowledge Level, Stress, Diet Compliance and Quality of Life in Gastritis Patients - Yudisa Diaz Lutfi Sandi; Ade Fitriani; Lilis Lismayanti; Yanti Srinayanti; Wina Widianti (Inspirasi Foundation, 2021)
Introduction: Swelling of the mucosa in the stomach caused by inflammation due to irritation and infection is called gastritis. Gastritis can cause bleeding in the stomach, if not treated immediately will cause hemorrhagic shock. This study aims to determine the relationship between the level of knowledge, dietary compliance, stress, and quality of life in gastritis sufferers. Method: This research uses quantitative analytic research with cross sectional approach and the sampling technique uses purposive sampling technique, the number of respondents is 30 people in Cijeungjing Village, Cijeungjing District, Ciamis Regency. instrument research used a gastritis knowledge level questionnaire that had been tested for validity and reliability as many as 20 questions to measure the level of knowledge in gastritis sufferers, Comstock scale questionnaire measure the level of dietary compliance in gastritis sufferers, the PSS-10 questionnaire with 10 questions to assess stress. and the 26 questions WHOQOL-BREF questionnaire measure the quality of life. Analyze adopt Chi Square test. Result: Univariate analysis of each variable showed that respondents have a level of knowledge above the average on 22 people (73.3%), high levels of dietary compliance on 15 people (50%), severe stress levels on 11 people (36.7%) and a good quality of life on 16 people (53.3%). Conclusion: There is a significant relationship between stress levels and quality of life as evidenced by the results of statistical tests >ρ value (0.05> 0.029) and chi squared (X²) count < chi squared (X²) table (4,866<12,592) but there is no significant relationship between other variables.